(untitled) (Emancipação, 2023)
This article presents the results of a study that deals with teaching unionism in higher education at state universities in Paraná. Its aim is to discuss teaching unionism in higher education in its relationship with the political-legal movement that culminated in the enactment of the General Law for Universities (State Law No. 20,933/2021). In order to meet the proposed objective, two methodological approaches were chosen: the first is related to the documentary analysis of the reports of two state seminars organized by the teaching unions for the purpose of debating the drafts of the LGU and also the notes/bulletins/manifestos published by the Teaching Union Command; the second used the oral history through the testimony of union professors who exposed their interpretations on the mentioned law and the probable repercussions for the state system of higher education in Paraná. The main results were the unions’ rejection of and resistance to LGU, which they considered to be damaging, among other things, to university autonomy. In addition, this rejection can be understood in relation to historical elements of trade unionism in the state.